Study the Effect of Electrospinning Device Room Temperature on Electro-spun PVA Nano-fibers - Tuhmaz, Ghazal; Issa, Manal; Bakr, Husain (Nahrain University College of Engineering Journal, 2017)
This research focuses on studying the effect of electrospinning device room temperature on PVA nano-fibers diameter made by electrospinning device depositing on rotating drum. In this research, the preparation of nano-non woven fabrics by electro-spun polymer solution of poly vinyl alcohol using distilled water as solvent in temperature range [15-35]C° was achieved. The relative humidity 40%, polymer solution concentration 14% wt., voltage 22KV, tip-to-collector distance 10 Cm. The results of the five scanned samples by scanning electron microscope (SEM) indicated that: by increasing room temperature the diameter of nano-fibers decreased. Also it is important to mention that the range of room temperature shouldn't be exceeded in order not to close the orifice of the needle because of the evaporation of the droplet solvent changing into solid polymer.